Emotion and birth control: Emotion regulation ERPs differ based on menstrual cycle phase and hormonal contraceptive use - Doornweerd, Anne Marieke; Baas, Joke M.P.; Montoya, Estrella R.; van de Vijver, Irene; Gerritsen, Lotte (Psychoneuroendocrinology, 2024)
While hormonal contraceptives (HCs) like oral contraceptive pills (OCs) and intrauterine devices (IUDs) can reportedly influence mood, the evidence is mixed, and the mechanisms remain unclear. Emotion reactivity and regulation processes may be hormone-sensitive and underlie these mood changes. This study sought to investigate the role of the menstrual cycle and HC use in emotion regulation using ERP measures during an emotion regulation paradigm. Participants with a natural cycle (NC) were measured in the mid-follicular and mid-luteal phase (within-subject design, n = 26), and compared with OC (n = 36) and IUD (n = 25) users. The centroparietal late positive potential (LPP) reflected negative emotion reactivity and its modulation by cognitive reappraisal served as a marker for emotion regulation processing. NC participants had a lower LPP amplitude in the mid-luteal compared to the mid-follicular phase. Reactivity to negative emotional stimuli decreased over time in the mid-luteal phase, whereas the HC groups showed sustained LPP activation. Reappraisal led only to significant LPP changes in the mid-follicular phase, and not in the mid-luteal phase or HC groups. Our results showed a specific left frontal activity (FR-LPP) in the contrast that reflected emotion regulation processing. This activity was highest in the mid-follicular phase, and was significantly different from the OC users but not from the IUD group. Higher self-reported PMS symptoms were associated with stronger effects on the reduced mid-luteal LPP activity and with lower FR-LPP amplitude in the mid-follicular phase. No effect of OC phase (active pill use versus pill pause) was found. These findings add insights into the neurophysiological underpinnings of hormone-related mood changes and demonstrate the importance of considering hormonal status and PMS symptoms in emotion research. •Blunted LPP reactivity in the luteal phase, driven by high PMS ratings.•Emotion regulation modulated LPP only in the follicular phase, mostly with low PMS.•Highest frontal regulation LPP (FR-LPP) in the follicular phase, lowest in OC users.•OC users, but not IUD users, show altered FR-LPP compared to NC participants.•No differences in subjective emotion ratings between NC individuals and HC users.